2010
DOI: 10.1002/hyp.7893
|View full text |Cite
|
Sign up to set email alerts
|

Trends in rainfall and runoff in the Blue Nile Basin: 1964–2003

Abstract: Most Nile water originates in Ethiopia but there is no agreement on how land degradation or climate change affects the future flow in downstream countries. The objective of this paper is to improve season flow. The difference in response was likely due to weir construction in the nineties at the Lake Tana outlet that affected significantly the upper Blue Nile discharge but only affected less than 10% of the discharge at the Sudan border. The rainfall runoff model reproduced the observed trends, assuming that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 36 publications
7
103
2
1
Order By: Relevance
“…In the more recent period (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)) the 13% degraded area gives the best fit to the observed data (slope of the regression line close to 1) compared with the 5% degraded area that under predicted the sediment concentration. Similar analysis for the Blue Nile basin showed the same trends (Tesemma et al, 2010; Steenhuis and Tilahun, 2014) where direct runoff and sediment increased and sediment concentration with time that could be related to an increase in the proportion of degraded areas. This is strengthening this type of analysis.…”
Section: Saturation Excessmentioning
confidence: 59%
“…In the more recent period (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)) the 13% degraded area gives the best fit to the observed data (slope of the regression line close to 1) compared with the 5% degraded area that under predicted the sediment concentration. Similar analysis for the Blue Nile basin showed the same trends (Tesemma et al, 2010; Steenhuis and Tilahun, 2014) where direct runoff and sediment increased and sediment concentration with time that could be related to an increase in the proportion of degraded areas. This is strengthening this type of analysis.…”
Section: Saturation Excessmentioning
confidence: 59%
“…Conway and Hulme (1993) reported declining annual rainfall over the Blue Nile and Atbara basins, resulting in a reduction of river flows between 1945 and 1984. In contrast, recent investigations by Tesemma et al (2010), Tekleab et al (2013) and Gebremicael et al (2013) agreed that rainfall over the Upper Blue Nile Basin did not show a statistically significant trend for the last 40 years . Despite the fact that the pattern of rainfall remained constant, hydrological flows in the basin showed a heterogeneous trend.…”
Section: Introductionmentioning
confidence: 75%
“…Many studies (e.g. IPCC, 2013;Shi et al, 2013;Tekleab et al, 2013;Tesemma et al, 2010;Zhao et al, 2015) have shown that rainfall is the primary atmospheric factor that directly affects the streamflow patterns. The impact of climate change on hydrology varies from place to place.…”
Section: Introductionmentioning
confidence: 99%
“…For studies in the Lake Tana basin we refer to Solomon et al (2010) who focused on hydrologic impacts of deforestation in the Koga catchment that directly neighbors the Gilgel Abbay catchment and to Tesemma et al (2010) who focused on trends in rainfall and runoff for selected areas in the Blue Nile. Part of the latter study focused on the Lake Tana basin area but establishing clear effects of land use changes was not possible since hydrologic assessments focused on the outflow of Lake Tana instead of stream flows from catchments that drain to the lake.…”
mentioning
confidence: 99%